A STUDY OF THE TASTE SENSITIVITY THRESHOLD TO THE SALT AS ONE OF ARTERIAL HYPERTENSION RISK FACTORS IN SCHOOLCHILDREN OF TYUMEN - E. I. Gakova; E. V. Akimova; V. A. Kuznetsov (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To study the prevalence of the taste sensitivity threshold for salt (TSTS) as one of the main risk factor for hypertension in Tyumen city schoolchildren.Material and methods. The single-period epidemiologic study conducted in the population of 7-17 y. o. schoolchildren from one of the districts of Tyumen (2004-2006), chosen by a random assignment method, with a quantity of 2640 persons (1308 boys, 1332 girls), with response rate 87,7%. In schoolchildren of 9-17 y. o. (880 boys, 936 girls), the TSTS measured using modified Henkin R et al. method (described by Konstantinov E. N. et al., 1983).Results. The prevalence of high level of TSTS in a population of schoolchildren was 14,8%, average TSTS had 75,8% of schoolchildren, in 9,5% of persons low TSTS was identified. Persons with high TSTS were met almost in 2 times often among boys compared with girls, and in 1,5 times among adolescents with simultaneously elevated systolic and diastolic blood pressure (BP), than among schoolchildren with normal BP levels (p<0,05).Adolescents 14-17 years of age with elevated diastolic blood pressure were observed higher tangible medium salt concentration. The relation between TSTS and the degree of increase in blood pressure in adolescent’s, from medium to strong, was revealed by paired correlation analysis.Conclusion. The results showed high prevalence of the high TSTS in Tyumen schoolchildren population, relation between TSTS and the severity of BP increase in youths.